Visualising file-systems using ENCCON model - Quang V. Nguyen; Mao L. Huang (VIP'04: Proceedings of the Pan-Sydney Area Workshop on Visual Information Processing, 2004)
This paper describes a new approach for visualising the file structures. Our technique uses an enclosure + connection (ENCCON) approach that provides an overall view of the entire file/directory hierarchy that gives a better understanding of the folder-folder and folder-file relationships, and therefore makes easier for the navigation. We firstly use the rectangular regions to present the folders. This allows the user to immediately percept the location, size (number of files contained) and other properties of any particular folder. To enrich the visual attributes of the file structure, we also use a node-link diagram to present the "belonging" relationships. This "belonging" relationship includes folder-folder and folder-file relationships. We use a semantic zooming technique to enlarge the display of files and folders in a particular focused area. The animation is also accommodated in order to preserve the mental map [Bartram 1997] during the navigation.